Government subsidisation and shareholder wealth impact: Evidence from Malaysia - Philip Sinnadurai; Ravichandran K. Subramaniam; S. Susela Devi; Young Kyung Ko (Journal of Risk and Financial Management, 2021)
This paper investigates the shareholder wealth impact of government investment in listed companies (and by extension, government subsidisation of those companies), using data from Malaysia. We distinguish two overlapping categories of government-related investors: those whose principal mission relates to economic policy and those whose principal mission relates to social policy. The methodology entails Ordinary Least Squares regressions. There are two dependent variables measuring management success at generating shareholder wealth: an intrinsic value surrogate and return on equity. The final sample comprises 1732 company-year observations from the investigation period 2011-2014. The evidence indicates that companies subject to shareholder by a government-related investor with a social (economic) policy mission are more (less) successful at generating wealth than companies without any government shareholding at all. The findings indicate that for companies subject to ownership by government investors with a mission related to economic policy, government subsidies are wealth-enhancing, subject to diminishing marginal returns beyond a threshold level of government shareholding. The research design reflects adaptations to the Malaysian institutional setting via choice of control variables and usage of data from a leading Malaysian equity analyst.
Keywords: 330; government shareholding; government subsidisation; Malaysia; shareholder wealth